Assessing the Impact of Human Activities on Water Quality Parameters of River Kiruruma in Kabale District. - Tugume, Alex (Kabale University, 2024)
A comprehensive study was found to evaluate the concentration of different water qualities in the Kiruruma River. Samples were collected from five points (Rwakaraba, Rugarama, Riverside Resort, Jack& Jill, and Nyabikoni SS) in the Nyabikoni water shade during the Hydrological month of October for water quality assessment. Collected samples were analyzed to find some physicochemical parameters Temperature, pH, Alkalinity, Acidity, Total hardness, Sulphate, Chloride, Total Dissolved Solids (TDS), and phosphorus. The investigated parameters were compared to the national and international standards. The mean values of water Temperature, pH, Alkalinity, Acidity, Total hardness, Sulphate, Chloride, TDS, and phosphorus were found to be 28.36° C, 6.25, 275.63ppm, 19.75ppm, 259.29ppm, 70.74ppm, 534.63ppm, 778.83ppm & 0.904ppm, respectively. Water Quality Index (WQI) values were found to be 99.92, which indicates that the water quality is not good.